1991
DOI: 10.1139/b91-184
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms producing plant zonation along a water depth gradient: a comparison with the exposure gradient

Abstract: A 15-month field experiment was performed in the emergent zone of a freshwater riverine marsh along the Ottawa River, Canada, to determine whether the mechanisms producing plant zonation along the exposure gradient of freshwater shorelines also accounted for the zonal pattern along the water depth gradient. Three species (Carex crinita, Acorus calamus, and Typha angustifolia) were chosen, having contiguous distributions along a gradient of water depth. Ramets of each were planted within and beyond the field di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 14 publications
9
43
0
Order By: Relevance
“…Hydrology is also linked to other factors (exposure, litter accumulation, fertility gradients, exotic species introduction) previously shown to influence the complex mosaic of wetland plant assemblages (Day et al, 1988;Keddy, 1989;Shipley et al, 1991;Lavoie et al, 2003). Comparison of wetland assemblages over low-level episodes in 1931 and 1999 revealed that recent wetland plant assemblages reflect nutrient enrichment, drier wetland conditions and proliferation of aggressive taxa (Hudon, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrology is also linked to other factors (exposure, litter accumulation, fertility gradients, exotic species introduction) previously shown to influence the complex mosaic of wetland plant assemblages (Day et al, 1988;Keddy, 1989;Shipley et al, 1991;Lavoie et al, 2003). Comparison of wetland assemblages over low-level episodes in 1931 and 1999 revealed that recent wetland plant assemblages reflect nutrient enrichment, drier wetland conditions and proliferation of aggressive taxa (Hudon, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the hierarchy of causes has been controversial, because the effects of environmental factors on species and habitats differ, and many factors are correlated (van Diggelen et al 1996). Experiments by Shipley et al (1991) suggest that the mechanisms contributing to plant zonation along a freshwater depth gradient are not the same as the mechanisms producing zonal patterns along the exposure gradient as described by Wilson and Keddy (1986). Species order along a water depth gradient may be due instead to the different physiological response of each species modifi ed by interspecifi c competition, that the stresses at each depth are species-specifi c (Shipley et al 1991).…”
Section: Gradients and Patternsmentioning
confidence: 99%
“…Experiments by Shipley et al (1991) suggest that the mechanisms contributing to plant zonation along a freshwater depth gradient are not the same as the mechanisms producing zonal patterns along the exposure gradient as described by Wilson and Keddy (1986). Species order along a water depth gradient may be due instead to the different physiological response of each species modifi ed by interspecifi c competition, that the stresses at each depth are species-specifi c (Shipley et al 1991). Menges and Waller (1983) examined the distribution of herbaceous species in southern Wisconsin fl oodplain forest in relation to elevation and concluded that most species had defi nite elevation optima.…”
Section: Gradients and Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower distribution limits are abiotically constrained by flooding stress (Vervuren et al 2003;van Eck et al 2004), which strongly affects plant performances by reducing gas exchanges between plant and atmosphere (Crawford and Brändle 1996;Dat et al 2004). In contrast, competition is recognised as the most important factor at the upper distribution limits (Grace 1990;Keddy 1990, Shipley et al 1991Budelsky and Galatowitsch 2000), although studies suggested that drought might contribute to restrict flood-tolerant species to low elevations (Silvertown et al 1999;Lenssen and de Kroon 2005). Consequently, as flooding gradients would correspond to a shift from abiotic to biotic constraints, the intensity of stress induced by a change in hydrology should differ according to the direction of change.…”
Section: Introductionmentioning
confidence: 99%